2017
DOI: 10.3989/gya.0813162
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of selected plant-based shortening as lard substitute: microstructure, polymorphic forms and textural properties

Abstract: SUMMARY:A study was carried out to determine the compatibility of three plant-based shortening mixtures to lard shortening (LD) in terms of microstructure, polymorphic forms, and textural properties. The shortenings of binary, ternary, and quaternary fat mixtures were prepared according to a standard procedure by blending mee fat (MF) with palm stearin (PS) in a 99:1 (w/w) ratio; avocado fat (Avo) with PS and cocoa butter (CB) in a 84:7:9 (w/w) ratio; palm oil (PO) with PS, soybean oil (SBO) and CB in a 38:5:5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…When roughly 10% PO shortening is added during bread baking, data show that it enhances bread volume and oven spring to an optimal level of 4% ( Chin et al., 2010 ). Yanty et al. (2017) also discovered that shortening prepared from a blend of PO, soybean oil, and lipids had similar consistency, hardness, compression, and adhesiveness as lard shortening.…”
Section: Applications Of Palm Oil In the Food Industrymentioning
confidence: 95%
“…When roughly 10% PO shortening is added during bread baking, data show that it enhances bread volume and oven spring to an optimal level of 4% ( Chin et al., 2010 ). Yanty et al. (2017) also discovered that shortening prepared from a blend of PO, soybean oil, and lipids had similar consistency, hardness, compression, and adhesiveness as lard shortening.…”
Section: Applications Of Palm Oil In the Food Industrymentioning
confidence: 95%
“…The confirmed peaks were reported as peak area percentages. The TAG analysis was performed in triplicates (Yanty et al, 2017).…”
Section: Triacylglycerol Analysis Of Fish Feedmentioning
confidence: 99%
“…Additionally, these methods are costly for maintenance in testing laboratories (Abbas et al, 2018). Due to these disadvantages, affordable analytical methods using high-performance liquid chromatography refractive index detector (HPLC-RI) and differential scanning calorimeter (DSC) (Naquiah et al, 2017) have successfully identified lard adulteration by analysing the triacylglycerols (TAGs) and thermal properties (TPs) of the samples (Azir et al, 2017;Noorzyanna et al, 2017;Yanty et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these methods are costly for maintenance in testing laboratories (Abbas et al, 2018). Due to these disadvantages, affordable analytical methods using highperformance liquid chromatography refractive index detector (HPLC-RI) and differential scanning calorimeter (DSC) (Naquiah et al, 2017) have successfully identi ed lard adulteration by analysing the triacylglycerols (TAGs) and thermal properties (TPs) of the samples (Azir et al, 2017;Noorzyanna et al, 2017;Yanty et al, 2017). Nonetheless, these identi cation methods were inadequate for authentication purposes since the lard adulteration was identi ed using sample pro ling only.…”
Section: Introductionmentioning
confidence: 99%